A Naïve Framework for Responsible Business Innovation - Khairil Annuar, Mohd Kamal (Humanistic Management Network Research Paper, 2015)
In this paper I consider a framework to analyze how a firm may engage with a stakeholder with regards to responsible business innovation. In this simple framework, I present how a weak and relatively powerless stakeholder and a more powerful firm interact with each other, given that the firm has violated an ethical standard vis-á-vis that stakeholder in relation to business innovation. This framework is still at the naïve stage, but it will be a useful starting point for future research in stakeholder engagement particularly in issues concerning the sensitivity of firms and organizations towards their weak and powerless stakeholders.